From e-Commerce to m-Commerce: Trends and Developments in Mobile Technology - From e-Commerce to m-Commerce: Trends; Developments in Mobile Technology (International Journal of Innovative and Applied Finance, 2023)
login and register and pay the fees to get an open access to content